Humiliated fury is not universal: the co-occurrence of anger and shame in the United States and Japan. Issue 6 (18th August 2018) - Kirchner, Alexander; Boiger, Michael; Uchida, Yukiko; Norasakkunkit, Vinai; Verduyn, Philippe; Mesquita, Batja
ABSTRACT: It has been widely believed that individuals transform high-intensity shame into anger because shame is unbearably painful. This phenomenon was first coined "humiliated fury, " and it has since received empirical support. The current research tests the novel hypothesis that shame-related anger is not universal, yet hinges on the cultural meanings of anger and shame. Two studies compared the occurrence of shame-related anger in North American cultural contexts (where shame is devalued and anger is valued) to its occurrence in Japanese contexts (where shame is valued and anger is devalued). In a daily-diary study, participants rated anger and shame feelings during shame situations that occurred over one week. In a vignette study, participants rated anger and shame in response to standardised shame vignettes that were generated in previous research by either U.S. or Japanese respondents. Across the two studies, and in line with previous research on humiliated fury, shame predicted anger for U.S. participants. Yet, neither in the daily diary study nor for the Japanese-origin vignettes, did we find shame-related anger in Japanese participants. Only when presented with U.S.-origin vignettes, did Japanese respondents in the vignette study report shame-related anger. The findings suggest that shame-related anger is a culture-specific phenomenon.